Antibiotic Policies and Utilization in Oregon Hospice Programs. (September 2016) - Novak, Rachel L.; Noble, Brie N.; Fromme, Erik K.; Tice, Michael O.; McGregor, Jessina C.; Furuno, Jon P.
Antibiotics are frequently used in hospice care, despite limited data on safety and effectiveness in this patient population. We surveyed Oregon hospice programs on antibiotic policies and prescribing practices. Among 39 responding hospice programs, the median reported proportion of current census using antibiotics was 10% (interquartile range = 3.5%-20.0%). Approximately 31% of responding hospice programs had policies for antibiotic initiation, 17% of hospice programs had policies for antibiotic discontinuation, and 95% of hospice programs had policies for managing drug interactions. Diarrhea, nausea/vomiting, and yeast infections were the most frequently reported antibiotic-associated adverse events, occurring "sometimes" or "often" among 62%, 47%, and 62% of respondents, respectively. In conclusion, less than a third of participating hospice programs reported having a policy for antibiotic initiation and even less frequently a policy for discontinuation. More data are needed on the risks and benefits of antibiotic use in hospice care to inform these policies and optimize outcomes in this vulnerable patient population.